Effect of Thermal Stresses and Reduced Differential Transform on Bending of The Rectangular Plate - Chandrashekhar S. Sutar; Sandip N. Patil (Journal of the Indonesian Mathematical Society, 2021)
The bending of the rectangular plate exists for a large length comparing with its width as we have considered the simply supported plate. Also, it gets the accuracy, if the plate is attached between enough distance from the ends. This paper concern with the study of bending moment in the rectangular plate by using the thermal stresses. In this paper, we have considered the mathematical model of the unsteady state three-dimensional heat conduction equation for a thick rectangular plate with non-zero temperature initially. We have determined the thermal stresses and the bending moment in the rectangular plate by using the reduced differential transform method. The results are discussed by considering the special cases for copper material. Also, results are shown graphically. The graphs are drawn by using mathematical software Scilab.